Frequency of osteopenia and osteoporosis in patients with multiple sclerosis - Asadollahi, Marjan; Hamed, Zahra; Gharagozli, Kourosh; Atalu, Abolfazl; Nemati, Behzad (International Journal Of Community Medicine And Public Health, 2021)
Background: Multiple sclerosis (MS) is one of the most important diseases of the central nervous system and one of the main causes of disability in young and middle age groups. Recent studies show that the risk of osteoporosis and osteopenia in MS patients is higher than the normal population which could be related to many factors. The aim of this study was to determine the frequency of osteopenia and osteoporosis among MS patients. Methods: This descriptive cross-sectional study was performed on 30 patients with MS. Bone density of patients was assessed by bone mineral density (BMD) method. Necessary demographic and clinical information were collected by a checklist and then analyzed by statistical methods in SPSS version 16. Results: Of all patients, 36.7% had osteoporosis and osteopenia. According to the results, 86.6% of patients had a decrease in bone density in the pelvic region and 50% in the lumbar spine. 43.3% of patients had osteopenia in the pelvic region and 36.7% in the lumbar spine. Conclusions: The results showed that BMD was high in MS patients. Due to the problems of walking and lack of balance in these patients and the high probability of falling and fractures among them, paying attention to the problem of osteoporosis by early and repeated performing of BMD.